2020
DOI: 10.1186/s13041-020-00571-y
|View full text |Cite
|
Sign up to set email alerts
|

Diverged morphology changes of astrocytic and neuronal primary cilia under reactive insults

Abstract: Primary cilia are centriole-derived sensory organelles that are present in most mammalian cells, including astrocytes and neurons. Evidence is emerging that astrocyte and neuronal primary cilia demonstrate a dichotomy in the mature mouse brain. However, it is unknown how astrocytic and neuronal primary cilia change their morphology and ciliary proteins when exposed to reactive insults including epilepsy and traumatic brain injury. We used a double transgenic mouse strain (Arl13b-mCherry; Centrin2-GFP), in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 73 publications
(103 reference statements)
2
31
0
Order By: Relevance
“…These data suggest that there is a potential effect from blood proteins, when added into the media, enhances cell spread and/or cell reactivity. Astrocyte activation occurs in response to stimuli in an effort to repair the brain via proliferation and extension of astrocyte processes [37,38]. Perhaps increased concentration and type of protein adsorbed to the polydimethylsiloxane shunt surface enhances the receptor-integrin interplay and increases cell attachment, not just in cell number, but in cell affinity to the surface (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that there is a potential effect from blood proteins, when added into the media, enhances cell spread and/or cell reactivity. Astrocyte activation occurs in response to stimuli in an effort to repair the brain via proliferation and extension of astrocyte processes [37,38]. Perhaps increased concentration and type of protein adsorbed to the polydimethylsiloxane shunt surface enhances the receptor-integrin interplay and increases cell attachment, not just in cell number, but in cell affinity to the surface (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the current studies, 4 of 24 mice (16.5%) developed spontaneous seizures, and the duration of these seizures as well as their frequency progressed with time. Whereas only a minority of mice developed epilepsy, this was significantly different than chance, as a robust body of work has demonstrated that spontaneous epileptic activity is not found in control C57BL/6 mice 43–47 . Furthermore, the augmented susceptibility to KA in 56% of mice suggests that pro‐epileptogenic changes were initiated by eFSE in a larger proportion of mice.…”
Section: Discussionmentioning
confidence: 91%
“…Whereas only a minority of mice developed epilepsy, this was significantly different than chance, as a robust body of work has demonstrated that spontaneous epileptic activity is not found in control C57BL/6 mice. [43][44][45][46][47] Furthermore, the augmented susceptibility to KA in 56% of mice suggests that pro-epileptogenic changes were initiated by eFSE in a larger proportion of mice. Because we employed the C57BL/6 strain, these results are not surprising: It has long been recognized that C57BL/6 mice are resistant to the development of spontaneous seizures after an initial insult such as chemoconvulsant-induced status epilepticus.…”
Section: A Minority Of C57bl/6 Mice Develop Hippocampal Epilepsy Following Efsementioning
confidence: 99%
“…This indicates that the cells expressed on the sides are migrating from the cell layer along the bottom of the well up along the catheter. Astrocyte activation occurs in response to stimuli in an effort to repair the brain via proliferation and extension of astrocyte processes 37,38 . Perhaps increased concentration and type of protein adsorbed to the polydimethylsiloxane shunt surface enhances the receptor‐integrin interplay and increases cell attachment, not just in cell number, but in cell affinity to the surface (Figure 5).…”
Section: Discussionmentioning
confidence: 99%